Chemical Constituents of Desmos dunalii (Hk. f. et. Th.) Safford - Abdullah, Zanariah; Awang, Khalijah (Malaysian Journal of Science, 2005)
The leaves of Desmos dunalii were investigated for their chemical constituents. Four dihydrochalcones were isolated, namely, 2', 4-dihydroxy-4', 6'-dimethoxydihydrochalcone 1, 2', 4-dihydroxy-3', 6'-dimethyl-4' , 5'-dimethoxydihydrochalcone 2, 2', 4-dihydroxy-4', 5', 6'-trimethoxydihydrochalcone 3 and 2', 4'-dihydroxy-5'-methyl-4', 6'-dimethoxydihydrochalcone 4. The structures of these compounds were determined by spectral analysis: ¹H NMR, ¹³C NMR, 2D NMR and MS.